Effects of Methylprednisolone in the Treatment of Spinal Cord Injuries by Evaluation of microRNA-21: An Experimental Study - Abdallah, Anas; Tekin, Abdurrahim; Oztanir, Mustafa Namik; Süsgün, Seda; Yabacı, Ayşegül; Çınar, İrfan; Can, Engin; Tokar, Sadık; Akbaş, Fahri; Seyithanoğlu, Mehmet Hakan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background and Study Aims Spinal cord injury (SCI) is one of the most complicated pathologies that affect active young males. miR-21 primarily regulates several cellular processes. We aimed to elucidate the regulatory role of miR-21 and test methylprednisolone as a disease-modifying agent on experimental SCI tissues.Methods A total of 36 8- to 10-week-old adult female Sprague-Dawley rats weighing 250 to 300 g were used. Animals were randomly divided into six groups. Except for groups 1 and 4, the spinal trauma model was applied to all animal groups using the clipping method. In groups 3 and 6, methylprednisolone was given. For real-time polymerase chain reaction (PCR) investigations, rats in groups 1, 2, and 3 were reoperated on after the first postoperative day, whereas those in groups 4, 5, and 6 were reoperated on after postoperative day 7 and spinal cord samples from the laminectomy area were removed for gene expression analysis. Relative gene expression of miR-21, Gfap, Vim, Stat3, Faslg, Pten, Bax, Bcl2, Cox2, and Il6 were determined with quantitative reverse transcription (qRT) PCR.Results In group 3, the miR-21 expression significantly increased compared with groups 1 and 2. When compared with group 3, a decrease in miR-21 expression was observed in group 6 (p < 0.05). When compared with group 4, group 6 had lower levels of Gfap, Pten, Stat3, and Bax (p < 0.05).Conclusions miR-21 supports the beneficial aspects of the body's healing mechanisms following SCI. In the acute phase, the use of methylprednisolone increases miR-21 expression in the early period of trauma. Methylprednisolone increases some astrogliosis and inflammation biomarkers' levels; however, it did not affect the apoptotic biomarkers.
Keywords: spinal cord injury; miR-21; methylprednisolone; real-time PCR